The Relationship Of Family Knowledge With Preventing Decubitus Ulcers In Total Bedrest Patients In The Icu H. Sahudin Kutacane Hospital - Ade Kartika; Sri Mala Hayati (Sean Institute, 2023)
Decubitus is a problem faced by patients with chronic diseases, patients who are very weak and paralyzed for a long time, and is currently even experienced by many patients who are treated in hospitals, especially in ICU rooms. Comatose patients who undergo treatment in total bedrest for too long can cause tenderness and are at high risk of developing decubitus ulcers. This is due to the patient's inability to care for themselves or at least try to change their sleeping position, resulting in pressure on the same area for a long period of time. Efforts to prevent pressure ulcers should be carried out as early as possible since the patient is identified as being at risk of developing pressure ulcers. Therefore, the family plays a role in preventing the occurrence of decubitus ulcers in patients who experience total bed rest or patients who are in a coma in the ICU. The aim of this study was to determine the relationship between family knowledge and efforts to prevent decubitus ulcers in total bed rest patients in the ICU at H. Sahudin Kutacane Hospital. This research design is a correlative study. The population is the families of patients who experienced total bed rest in the ICU with a sample size of 40 people in October-November 2023. The research results found that the majority of families' knowledge was good, namely (72.5%). The risk of developing decubitus ulcers in the family is low, namely (45%). There were efforts to prevent decubitus ulcers in the families of total bed rest patients with a p value (p=0.002). Therefore, it is recommended that the patient's family should know and understand correctly about decubitus ulcers so that they can carry out treatment and prevention methods for decubitus ulcers in order to provide good care to patients on total bed rest in the ICU who are at risk of decubitus ulcers.